Two Inequalities and Two Means (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The paper presents geometric derivations of Jensen's and Hermite-Hadamard's inequality.Jensen's inequality is further involved to a concept of quasi-arithmetic means. Hermite-Hadamard's inequality is applied to compare the basic quasi-arithmetic means,